Risk Factors of Pneumonia Among Under Five Children in Purbalingga District, Central Java Province - Ni Kadek Nira; Dibyo Pramono; Roni Naning (Tropical Medicine Journal, 2013)
ABSTRACTIntroduction: Pneumonia is the leading cause of mortality and morbidity in young children and burden of disease disproportionately high in South-East Asia Region. Pneumonia incidence in Indonesia is sixth rank in the world.  Pneumonia were leading causeof infants mortality about 23.8% and among children, pneumonia contribute 15.5% of total mortality after diarrhea. Risk factors associated with pneumonia are: individual, environment, and social economic.Objectives: The aim of study to identify relationship between individual, environment, and social economic risk factors with pneumonia incidence among under five children in Purbalingga District.Methods: This research was an analytical and observational study using case control design. Subjects were 210 children aged 2-60 month which consists of 105 cases and 105 controls. This study conduct at 9 Public Health centers in Purbalingga District on April to June 2013. Cases were children with pneumonia diagnose by trained doctor or paramedic. Controls were children without diagnosed pneumonia who visited the same Public Health Centers as cases. Results fromunivariate, McNemar test was used to bivariate analysis and conditional logistic regression in multivariate analysis with 95% confidence interval.Results: In the multivariate analysis showednot exclusively breastfed (OR=3.99, 95% CI=1.851-8.596), househumidity (OR=3.13, 95% CI=1.382-7.096), house ventilation (OR=6.62, 95% CI=2.847-15.369), overcrowding (OR=2.74, 95% CI=1.230-6.121) and without kitchen smoke hole (OR=6.14, 95% CI=1.932-19.497) had significant association to pneumonia incidence. Ventilation showed the highest risk for pneumonia incidence among under five children.Conclusion: Factors such as not exclusively breastfed, live in house with high humidity, lack of ventilation, over crowding and without kitchen smoke holewere risk factors for pneumonia among under five children. Ventilation was dominant risk factor for developing pneumonia. Promote breastfeeding and improve house condition such as improve house ventilation and make kitchen smoke hole could lead to reduction of pneumonia under five children.Keyword: under five children, pneumonia, risk factors, Purbalingga District